Pictorial law modern law and the power of pictures - Boehme-Nebler, Volker 1962- (Springer, 2011)
We live in a digital media society, in which pictures are becoming more and more important. So, human communication is increasingly becoming a visual communication. That is not a new finding. But the new question is, what does this development mean for the law? Up to now the law is the part of the society which is most skeptical towards images. Law has still resisted the visual temptation. This will not last for ever. The rush of pictures in everyday life and in every part of the society is much too strong and it is even getting stronger. The invasion of images will change the character of modern law deeply. Modern law will become a Pictorial Law. What are the chances and the risks of Pictorial Law and visual law communication? This is the topic of the book